Doravirine and Its Potential in the Treatment of HIV: An Evidence-Based Review of the Emerging Data - Rock AE (Dove Medical Press, 2020)
Alexander E Rock,1 Jeremy Lerner,2 Melissa E Badowski1 1University of Illinois, College of Pharmacy, Department of Pharmacy Practice, Section of Infectious Diseases Pharmacotherapy, Chicago, IL 60612, USA; 2University of Illinois, College of Pharmacy, Department of Pharmacy Practice, Chicago, IL 60612, USACorrespondence: Melissa E BadowskiUniversity of Illinois, College of Pharmacy, Department of Pharmacy Practice, Section of Infectious Diseases Pharmacotherapy, 833 S. Wood, Room164, MC886, Chicago, IL 60612, USAEmail Badowski@uic.eduAbstract: The utility of doravirine in the management of HIV-1 infection is approved for use in patients who are antiretroviral-naïve as well as patients who have achieved stable virologic suppression and are interested in replacing their current antiretroviral therapy. The role of doravirine continues to evolve as data emerges on the potential for new combination therapy with the investigational agent, islatravir, as well as a potential strategy to minimize post-marketing safety concerns with recommended first-line agents, such as integrase inhibitors. The goal of this review is to assess recent and emerging data on the non-nucleoside reverse transcriptase inhibitor, doravirine.Keywords: doravirine, HIV-1, antiretroviral therapy, non-nucleoside reverse transcriptase inhibitor